2015
DOI: 10.1111/ggi.12454
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced vaccination effect against influenza by prebiotics in elderly patients receiving enteral nutrition

Abstract: Our findings suggest that prebiotics affect the intestinal microbiota and might maintain the antibody titers in elderly individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 32 publications
1
31
0
1
Order By: Relevance
“…Meta-analysis was performed using Review Manager (RevMan) [ Figure 1 shows the search process and outcomes. A total of 19 publications with 20 RCTs were included for our systematic review [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Two trials (a pilot and a confirmatory study) with different patient numbers, treatment protocols, and years of study were published together [35].…”
Section: Data Extraction and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Meta-analysis was performed using Review Manager (RevMan) [ Figure 1 shows the search process and outcomes. A total of 19 publications with 20 RCTs were included for our systematic review [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Two trials (a pilot and a confirmatory study) with different patient numbers, treatment protocols, and years of study were published together [35].…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…Two trials (a pilot and a confirmatory study) with different patient numbers, treatment protocols, and years of study were published together [35]. Thirteen trials focused on probiotics [22,[26][27][28][29][30][31][32][33][34][35][36], while the other six RCTs focused on prebiotics [23][24][25][37][38][39]. Only one study concentrated on synbiotics [21].…”
Section: Data Extraction and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…PF contains products obtained from milk fermentation by Lactobacillus bulgaricus and Streptococcus thermophilus, prebiotics such as galacto-oligosaccharides (GOS) and bifidogenic growth stimulator (BGS), and more water-soluble dietary fiber than that in standard formula (SF). In human clinical trials, elderly people who received PF as part of their enteral nutrition showed an increase in Bifidobacterium counts in their feces and an improvement in stool quality [10,11]. In addition, PF administration was associated with an increase in the number of Bifidobacterium in the cecum and SCFA levels in a rat enteral nutrition model [12].…”
Section: Introductionmentioning
confidence: 99%